Patterns of bird migration phenology in South Africa suggest northern hemisphere climate as the most consistent driver of change. (6th March 2015) - Bussière, Elsa M. S.; Underhill, Les G.; Altwegg, Res
Abstract Current knowledge of phenological shifts in Palearctic bird migration is largely based on data collected on migrants at their breeding grounds; little is known about the phenology of these birds at their nonbreeding grounds, and even less about that of intra‐African migrants. Because climate change patterns are not uniform across the globe, we can expect regional disparities in bird phenological responses. It is also likely that they vary across species, as species show differences in the strength of affinities they have with particular habitats and environments. Here, we examine the arrival and departure of nine Palearctic and seven intra‐African migratory species in the central Highveld of South Africa, where the former spend their nonbreeding season and the latter their breeding season. Using novel analytical methods based on bird atlas data, we show phenological shifts in migration of five species – red‐backed shrike, spotted flycatcher, common sandpiper, white‐winged tern (Palearctic migrants), and diederik cuckoo (intra‐African migrant) – between two atlas periods: 1987–1991 and 2007–2012. During this time period, Palearctic migrants advanced their departure from their South African nonbreeding grounds. This trend was mainly driven by waterbirds. No consistent changes were observed for intra‐African migrants. Our results suggest that the most consistent drivers of migration phenological shifts act in the northern hemisphere, probably at the breeding grounds.